Defensive behavior against crosses: An analysis of leading Spanish, English, and German elite football teams during the 2022 - 2023 season - Pafis, G.; Ispirlidis, M.-P.; Ispirlidis, I.; Malliou, V. J. (Journal of Physical Education and Sport, 2025)
The purpose of this study was to investigate the defensive behaviors of the top five teams in the Premier League, La Liga, and Bundesliga during national league matches in the 2022 - 23 season. A total of 60 football matches were analyzed, focusing on defensive responses to 1,428 crosses from open play. The goal was to identify effective strategies for defending crosses that enter the penalty area to minimize goal -scoring opportunities. For this study, the following tools were used: a) the Wyscout platform, b) P.C., and c) a tablet. Statistical analysis was performed using frequency analysis and percentages, with the Crosstabs command and the non-parametric chi-square (x2) test applied to examine relationships between the various categories. The tactical defensive behavior and the effectiveness of the defense in dealing with crosses concerned: 1) the body positioning of the defensive line players at the time of crossing, 2) the numerical defender-attacker relationship within the penalty area at the time of the cross, and 3) the cooperation of the defensive line and the midfielder. The analysis of the data showed that: 1) Defenders within the penalty area in all zones of the crosser choose in the highest percentage from 45.5% to 60.7% to have such a body position so that they "see the ball and the opponent". The effectiveness of the defense was statistically significant (p<0.05) in all zones of the crosser recording the highest success rates in the "see ball and opponent" situations. 2) The numerical ratio of defenders - attackers within the penalty area which appeared was mainly a preponderance of defenders over attackers in the range of 68.6% to 83%, secondly an equal number of defenders - attackers emerged in the range of 14% to 30.2% while the cases of minority of defenders the percentages ranged from 2.9% to 9.5% in all the zone of the crosser. In general, higher success rates were recorded in supernumerary versus equal number and minority situations. In terms of defensive effectiveness versus numerical relationship, a statistically significant difference (p<0.05) was found in the defenders' supernumerary situations for zone of the crosser LS: 26-16.5m, LS: 5.5-0 m. 3) Proper cooperation between defenders and midfielder increases success rates and decreases defensive line failure rates in all zone of the crosser. A statistically significant difference (p<0.05) in defensive effectiveness between correct and incorrect collaboration between defenders and halfbacks emerged for zone of the crosser LS: 26-16.5m, LS: 11-5.5m, LS: 5.5-0m, HS: 16.5-11m and HS: 5.5-0m. In conclusion, optimal body positioning, maintaining numerical superiority, and strong cooperation between defenders and midfielders are critical factors in successfully defending crosses in elite-level football.